PERANCANGAN LOAD BALANCE MENGGUNAKAN METODE ECMP (EQUAL COST MULTI PATH) PADA MIKROTIK ROUTERBOARD 750GR3 - I Nyoman Bernadus; Prastyadi Wibawa Rahayu; I Made Dwi Ardiada (J-ICON : Jurnal Komputer dan Informatika, 2022)
Internet speed at all times is very helpful in carrying out and completing tasks, especially for workers and students. A slow internet connection can be a very annoying thing if it happens continuously. For this reason, this study discusses how to take advantage of internet links by dividing the traffic load equally or called load balance by using the Equal Cost Multi Path (ECMP) method in order to produce a maximum flow of packages so as to avoid overload on one connection down. From the test results, it is found that applying the load balance system to the ECMP method, the traffic load on the two internet lines can be divided evenly, the connection tag on the Mangle automatically determines incoming and outgoing packet connections so as to maintain and increase the bandwidth speed of the internet connection.